The UK's Productivity Puzzle - Alex Bryson; John Forth (Institute for the Study of Labor (IZA), 2015)
The 2008 Great Recession was notable in the UK for three things: the enormity of the output shock; the muted unemployment response; and the very slow rate of recovery. We review the literature which finds most of the decline in productivity is within sector and within firm before presenting new micro-analysis of workplace-level behaviour between 2004 and 2011 to gain insights into the processes that may have contributed to this aggregate picture. We find clear evidence of labour intensification but employers appeared incapable of turning this effort into improved workplace level productivity. Widespread pay freezes and cuts were often initiated in direct response to the recession. Workplace closure rates were little different to those experienced prior to the recession, but there is some evidence of a "cleansing" effect with poorer performing workplaces being more likely to close. There is some evidence of labour "hoarding", especially hoarding of high skilled labour: this has had no discernible impact on the rate of innovation. There is no impact of recession on either the number of HRM practices workplaces invested in, nor their returns on those investments. There is no evidence that workplaces have benefited from Britain's "flexible" labour market as indicated by using recruitment channels used by welfare recipients or the use of numerically flexible workers. On the contrary, workplaces with increasing unionisation appeared to benefit in terms of improved workplace performance.
Keywords: D22; E22; E23; E24; J23; J24; J3; 330; productivity; recession